Optoelectronic and thermal properties of highly fluorescence emissive 2, 2′-distyryl-[3, 3′]-bithiophenes. (May 2017) - Cheng, Fengkai; Yin, Yan; Zhang, Guozhen; Wang, Yuan; Deng, Wei; Wu, Fanhong
Abstract: Five newly designed organic small molecules (DSBTs, 1 –5 ) with 3, 3′-bithienyl unit had been successfully synthesized with 3-bromothiophene as the starting material. In both UV–vis absorption and fluorescence emission investigation, compound3 with nitro-substitution exhibited the largest bathochromic shift and narrowest optical bandgap among1 –5 . Further photophysical studies showed that3 had obvious solvatochromism and aggregation-induced emission (AIE) property. The electrochemical properties and thermal stabilities studies demonstrated that3 had high electron affinity and good thermal stability, which in combination with favorable optical properties indicated the prospect of3 as a promising material in optoelectronic devices. Finally, theoretical calculations on structures, frontier molecular orbitals, UV–vis spectra and electronic transitions gave a good acknowledge of the relationship between optoelectronic properties and molecular structures. Graphical abstract: Obvious stokes shifts, solvatochromism and AIE behavior were observed. Highlights: 2, 2′-Distyryl-[3, 3′]-bithiophenes (DSTBs) were designed and synthesized. Compounds exhibited high UV–vis absorption, fluorescence emission and electron affinity, and good thermal stability. Theoretical calculation on structure, frontier molecular orbital, UV–vis spectra and electronic transition was performed.